ニホン ノ ナンキョク カンソク キチ ニオケル ヒョウセツ ジョウ ノ カッソウロ セッチ ノ カノウセイ ニツイテ トウナンキョク コウクウモウ コウソウ ニ カンレン シテ - 白石, 和行; シライシ, カズユキ; Klokov, Valery; Shiraishi, Kazuyuki (1997)
P(論文) 日本南極地域観測隊に大型航空機を導入して大陸間航空路を設けることの可能性を研究した。昭和基地, やまと山脈近傍の雪面や青氷上に, 車輪で離発着できる固い滑走路を建設できる場所を検討した結果を, その建設方法の概略や発着できる航空機の性能などとともに示した。さらに, 東南極航空網計画を国際的に推進することの必要性を説いた。 This report summarizes the feasibility study to introduce intercontinental air operation for the Japanese Antarctic Research Expedition (JARE) by establishing hard-surface runways near JARE stations. Syowa Station and the Yamato Mountains areas were considered to identify the favorable sites for run way construction on the basis of historical meteorological data and glaciological conditions. Techniques and logistic facilities for snow-ice runway construction, and the general characteristics of aircraft that are of practical interest in Antarctica are briefly outlined. Moreover, international collaboration to improve the East Antarctic Air Network is emphasized. departmental bulletin paper